The Natural Disaster Mitigation of Road and Bridge Infrastructure in Bogor Regency, West Java - Adityo, firman; Kusuma; Sugeng Tri Utomo (International Journal of Education, Vocational and Social Science, 2026)
Bogor Regency, West Java, is an area with high vulnerability to natural disasters, especially floods and landslides, which threaten the sustainability of its road and bridge infrastructure. This transportation infrastructure plays a vital role as the lifeblood of the economy and evacuation access. This research aims to analyze the disaster risk to road and bridge infrastructure in Bogor Regency and evaluate applied and potential mitigation strategies. The research methods include literature review, secondary data analysis (BPBD risk map, historical disaster data, planning documents), field observations focused on vulnerable locations, and interviews with stakeholders (BPBD, PUPR Office, community). The results showed that the main threats in the form of flash floods and inundation in the north-eastern region (Jonggol, Cileungsi, Citeureup sub-districts) and landslides in the hilly south-central region (Megamendung, Cisarua, Cijeruk, Leuwiliang sub- districts) caused structural damage, erosion, access breaks, and logistical disruptions. Existing mitigation strategies include the construction of physical structures (embankments, gabions, retaining walls, slope reinforcement), river normalization, drainage improvement, and installation of landslide early warning devices. However, challenges such as budget constraints, development pressure on catchment areas, infrastructure maintenance, and climate change dynamics still hamper their effectiveness. This research recommends an integrated approach: (1) Strengthening of high-risk based structures with erosion/inundation resistant materials; (2) Application of Nature-Based Solutions (NBS) such as intensive slope revegetation and biopores; (3) Integration of infrastructure- specific Early Warning Systems; (4) Application of the post-disaster "Build Back Better" (BBB) concept; (5) Cross-sector coordination and increased community participation in monitoring. Sustainable investment and strict spatial policies are key to resilient road and bridge infrastructure in Bogor Regency.